Urgensi Keterampilan Kolaborasi di Perguruan Tinggi: Penelitian - Sity Rahmy Maulidya; Sri Ulfa Insani (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
In order to prepare themselves for the world of work in the era of digitalization, it is important for students to develop collaboration skills. As the highest level of education, universities have a significant role to play in creating human resources that are competitive in the era of the 4.0 Revolution. The purpose of this study is to explain the importance of students developing collaboration skills that are relevant to the era of the 4.0 Revolution. With all the conveniences of information and communication technology, universities are expected to be able to optimize student learning oriented towards 6C skills, namely critical thinking, creativity, collaboration, communication, character, and citizenship. This research is qualitative in nature with a literature-based data collection method. The results of the study indicate that collaboration skills are important for students to develop in order to prepare themselves for the professional world. Collaboration skills are very useful for elaborating ideas/understanding, arguments, and creativity.